Kadar Antitrombin III Pada Trauma Berat Yang Dilakukan Operasi Hubungannya dengan Komplikasi Sepsis - Alexander Surya Agung, - (2002)
Background. Patients suffering from severe trauma are at great risk to progress into SIRS and sepsis. Released mediators underlie the inflammatory reaction and coagulopathy. AT Ill factors play an important role in inhibiting this process. Evidently, in severe trauma and sepsis AT ill serum level decreases significantly. Objective. To defme the correlation between AT III serum level with severe trauma, and predict outcome of illness and development of late infection. Materials and Methods. A prospective study involving 24 patients diagnosed with multi trauma was conducted through the period from December 2001 to February 2002, at Dr. Soetomo Hospital Surabaya. These patients were divided into three groups based on the Champion's Trauma Score (at the end, each group consisted of 8 patients). The following classification was applied :1. Mild and moderate traumas, act as the control group, 2. Severe trauma without sepsis, 3. Severe trauma with sepsis. Blood test were performed on these patients sequentially on the days I5 \ IIIrd and VIIth after the day of operation to measure AT III serum levels. Statistical significance between groups was determined by using the Student t-test and X2 analysis with Fischer's exact test. Differences were considered to be significant when p values were less than 0.05.Normal AT Ill serum level ranges from 75%- 120%. Results . . The mean average of AT III serum levels was 75.3% ± 16.6%. AT ill serum levels in patients with severe trauma (trauma score~ 9) without sepsis were 71.0% ± 14.4%, AT III serum levels in patients with severe trauma complicated with sepsis were 69.9% ± 25.4%.The low ATIII serum levels predisposed to an increased risk of infection and sepsis. Patients with severe trauma were significantly associated with decreased AT ill levels (p=0.03) which served as a predictor of sepsis (p=0 .028). Conclusion. AT Ill serum levels may contribute in predicting infection in the outcome of severely injured patients.